2022
DOI: 10.1177/17456916221112077
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Uncertainty in the Neural Distinction Between Social and Nonsocial Thought

Abstract: Neuroimaging research has identified a network of brain regions that is consistently more engaged when people think about the minds of other people than when they engage in nonsocial tasks. Activations in this “mentalizing network” are sometimes interpreted as evidence for the domain-specificity of cognitive processes supporting social thought. Here, we examine the alternative possibility that at least some activations in the mentalizing network may be explained by uncertainty. A reconsideration of findings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 86 publications
1
10
0
Order By: Relevance
“…In Experiments 1 and 2, we showed that, when little information about the social environment is provided, participants demonstrated more exploration in a social versus nonsocial context. Enhanced exploration is consistent with the idea that social contexts present additional uncertainty (Berkay & Jenkins, 2023) that, in the absence of other social information, learners attempt to resolve through search and sampling of options. In Experiments 3 and 4, we observed that enhanced exploration in a social context can be reduced by providing relevant social information.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In Experiments 1 and 2, we showed that, when little information about the social environment is provided, participants demonstrated more exploration in a social versus nonsocial context. Enhanced exploration is consistent with the idea that social contexts present additional uncertainty (Berkay & Jenkins, 2023) that, in the absence of other social information, learners attempt to resolve through search and sampling of options. In Experiments 3 and 4, we observed that enhanced exploration in a social context can be reduced by providing relevant social information.…”
Section: Discussionsupporting
confidence: 78%
“…In concert, the limitations and future directions highlight the idea that there are likely many mechanisms underlying the differences between social and nonsocial contexts. In other words, the "socialness" of a context will contain myriad features, including heightened uncertainty (see Berkay & Jenkins, 2023 for an in-depth examination of this idea), but perhaps also heightened stakes for rewards receipt or other features. As one step to understanding additional features, we conducted one additional experiment-"Experiment 5" (see the online supplemental materials) to investigate a possible role in individuation of the reward-generating entities.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Autism is associated with elevated levels of intolerance of uncertainty, which mediates between autistic traits and anxiety ( Boulter et al, 2014 ; Vasa et al, 2018 ; Jenkinson et al, 2020 ). It has recently been suggested that social situations are difficult for autistic individuals precisely because of their inherently uncertain nature (rather than their social nature per se , Berkay and Jenkins, 2022 ).…”
Section: Discussionmentioning
confidence: 99%